A RCT to evaluate a totally automated, culturally-adapted telephone counselor for increasing physical activity among physically inactive individuals in China - Lancelot W. H. Mui; Robert H. Friedman; Joseph T. F. Lau; Ji Peng; Abu S. Abdullah (BMC, 2018)
Abstract Background The prevalence of diabetes in China has rapidly increased in recent years. Family history and physical inactivity are known risk factors for developing diabetes. As automated telephone-based communication is recognized as a cost-effective health promoting device, the present study aims at evaluating the efficacy of an automated telephone counselor (TLC-PA-China) for promoting physical activity to the WHO-recommended level among physically inactive family members of diabetes patients. Methods This study employed a parallel, two-group, non-blinded, randomized controlled trial design with equal allocation to the intervention group (TLC-PA-China), and a control group. Voluntary participants with at least one first-degree relative diagnosed with diabetes mellitus were recruited through eight Community Health Centers in Shenzhen, China. The intervention group was requested to use the system once per week during a six-month period. The control group received an information pamphlet about the benefits of regular physical activity. Results Two hundred ten eligible participants were randomized to TLC-PA-China (n = 109) or Control (n = 101) groups. Using intention-to-treat analysis, the TLC-PA-China group was significantly more likely to meet the WHO physical activity recommendation than the control (GEE: OR = 6.37, p < 0.001). The number of physically inactive people to intervene upon for one to become active was 2.84 at 3 months and 3.31 at 6 months. Conclusions TLC-PA-China increased physical activity levels among physically inactive adults in China who were at high risk of developing diabetes. This study lays the groundwork for application of behavioral informatics intervention in China. Trial registration Chinese Clinical Trial Registry ChiCTR-PRC-13003361. Registered 15 May 2013 (Retrospectively registered).